The Taxonomic Affinity of 7 members of Rutaceae Based on Morphological Characters - Septiana, Melysa; Kurniasari, Anggun; Putri, Shafa Adilah Japa Nugroho; Akmalia, Hafidha Asni; Al Faroqi, Nisa Amaliyah Rohmah (Tadris Biologi, Tadris Fisika, and Tadris Kimia, Universitas Islam Negeri Antasari, 2024)
This research aims to determine the taxonomic affinity of 7 members of Rutaceae based on morphological characters. There are 7 species observed namely Aurantifolia swingle, Citrus hystrix, and Citrus maxima, Citrus limon, Muurraya paniculate, Limonia acidissima, and Citrus paradis. We used 13 morphological characters including leaf surface, leaf tip, leaf base, leaf margin, flower color, crown shape, number of petals, rind, fruit shape, flesh of fruit’s color, rind’s color, fruit apex’s shape, and stem surface. Analysis using NTSYS showed that Aurontifolia swingle and Citrus paradisi share the most widely characters in leaf surface, leaf tip, leaf base, leaf margin, flower color, number of petals, fruit shape, rind’s color, and stem surface with a similarity coefficient is 0.69. This finding gives an insight that morphology still could be used in grouping species based on their similarity. We recommended to add more species in Rutaceae as well as increase the number of morphological characters to get a comprehensive data.